Romania's Digital Divide and the Failures of E-Government - Sorin Dan ŞANDOR (Transylvanian Review of Administrative Sciences, 2006)
This paper tries to measure the level of the digital divide existing in Romania and also to verify its relationship with e-government. At the country level, Romania is one of the least digitally developed countries in Europe, but it has shown a sharp increase in recent years. At the social level, based on data from public opinion surveys, digital divide is analyzed at two levels: lack of access and lack of knowledge. The results are similar to those in other countries: digital divide appears along the same dimensions: rural/urban, age, education, wealth and, to a lesser extent, gender. E-government services, while presumed to be at an adequate level, are used only by a very small number of citizens, thus having no impact upon the digital divide. Confronted with a serious divide, and with great possibility of its increasing, Romania needs to promote policies designed to increase access and knowledge. Also, e-government is not possible, unless administrative culture and procedures change.